2000
DOI: 10.1046/j.1469-0705.2000.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cardiac systolic and diastolic function: relationship with uteroplacental resistances. A Doppler and echocardiographic longitudinal study

Abstract: Diastolic cardiac function varies during pregnancy. A relationship between preload (left atrial enlargement), afterload (RI reduction), morphologic, and diastolic function modifications (IVRT reduction, DtE prolongation) appears to exist as a consequence of the hemodynamic modifications which occur during physiologic pregnancy. Diastolic function analysis maybe useful to identify women who fully adapt to pregnancy, and to understand the mechanisms that might be involved in women who show abnormal uterine arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
120
1
12

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(148 citation statements)
references
References 0 publications
15
120
1
12
Order By: Relevance
“…In physiological pregnancies, reduction in uteroplacental resistance index, because of the remodelling of the spiral artery, is concomitant with a decrease in TVR, which represents the steady component of the afterload, and includes the uteroplacental circulation with a contribution of 20% to 26% to the total reduction of systemic vascular resistance in the second trimester. 16 Abnormal uterine artery Doppler waveforms during the second trimester of pregnancy have been linked to an altered trophoblast invasion of the spiral arteries with an abnormal placentation process and seem to be related to several disorders of pregnancy, such as FGR and preeclampsia. In the last decade, an altered cardiovascular adaptation was noted in patients with such complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In physiological pregnancies, reduction in uteroplacental resistance index, because of the remodelling of the spiral artery, is concomitant with a decrease in TVR, which represents the steady component of the afterload, and includes the uteroplacental circulation with a contribution of 20% to 26% to the total reduction of systemic vascular resistance in the second trimester. 16 Abnormal uterine artery Doppler waveforms during the second trimester of pregnancy have been linked to an altered trophoblast invasion of the spiral arteries with an abnormal placentation process and seem to be related to several disorders of pregnancy, such as FGR and preeclampsia. In the last decade, an altered cardiovascular adaptation was noted in patients with such complications.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, maternal cardiac function was studied in normal and complicated pregnancy obtaining important information on systolic and diastolic function and on morphological parameters of the left ventricle. [13][14][15][16][17][18][19][20][21][22][23] In particular total vascular resistance (TVR) was found to be an important parameter in the early identification of hypertensive patients who subsequently developed complications. 22 In our previous pilot study, 24 we observed that normotensive high-risk patients with bilateral notch of the uterine arteries who subsequently showed abnormal outcome of pregnancy had higher TVR compared with the normal-outcome group.…”
mentioning
confidence: 99%
“…14,15 Although the uterine vascular bed has a specific and well-established role in the physiological adaptation of the whole maternal peripheral vasculature, 27,28 and in the genesis of hemodynamic alterations in pregnancy, this parameter does not appear to be an independent predictor when analyzed together with the cardiac parameters. In our model, concentric geometry results were the strongest independent predictor of adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological gestation is accompanied by significant adaptations in maternal hemodynamics, both in women and in female dogs (DUVEKOT et al, 1993) and these ensure adequate uterine perfusion and consequently normal fetal development (VALENSISE et al, 2000;BLANCO et al, 2008). Results of the hemodynamic adaptations involving the cardiovascular system in mammals are very similar (DESAI et al, 2004;BLANCO et al, 2011).…”
Section: Gestational Hemodynamicsmentioning
confidence: 99%